PCP4 inhibits the progression of prostate cancer through Ca2+/CAMKK2/AMPK/AR pathway - Jia, Wenqiao; Yu, Zeyuan; Sun, Feifei; Liu, Ping; Han, Bo (Frontiers in Immunology, 2025)
BackgroundThe development of prostate cancer (PCa) remains a major health threat for men worldwide. Calcium/Calmodulin signaling pathway has been implicated to the initiation and progression of diverse human cancers. Loss or downregulation of Purkinje cell protein 4 (PCP4), is frequently observed in some prostate cancer patients, particularly those with castration-resistant prostate cancer (CRPC).MethodsPublic datasets were used to analyze PCP4 expression and the relationship between PCP4 expression and clinicopathological characteristics of PCa patients. Gain- and loss-of-function studies in PCa cell lines and mouse models were performed to characterize the role of PCP4 in tumor progression. A series of molecular and biochemical experiments were carried out in PCa cell lines to investigate the mechanism underlying PCP4-mediated tumor suppression.Results(1) PCP4 gene loss occurs at high frequency in PCa patients, and decreased expression of PCP4 correlates with poor prognosis of PCa, particularly CRPC development; (2) TMPRSS2-ERG fusion frequently co-occurs with PCP4 deletion; (3) PCP4 suppresses prostate cancer progression in vitro and in vivo; (4) PCP4 is an androgen receptor (AR) suppressed gene; (5) PCP4 was involved in the stabilization of CAMKK2 protein; (6) PCP4 inhibits PCa progression by regulating Ca2+/CAMKK2/AMPK/AR signaling axis.ConclusionOur findings elucidate the molecular mechanism that PCP4 downregulation promotes PCa progression via Ca2+/CAMKK2/AMPK/AR pathway, highlighting its significance in CRPC development.